Navigating self-injury in a digital world: adolescents’ perspectives on coping, help-seeking, and technology - Israel Ramirez; Olga Barnas; David C. Mohr; Madhu Reddy; Jason J. Washburn; Theresa Nguyen; Kaylee P. Kruzan (Frontiers in Digital Health, 2026)
Background Nonsuicidal self-injury (NSSI), hereafter referred to as self-injury, is common among adolescents and is associated with elevated risk for suicide attempts and other adverse mental health outcomes. Because most adolescents who self-injure do not receive formal treatment, accessible alternatives are needed. Digital mental health interventions (DMHIs) may offer an accessible and scalable means of support. While previous research has examined DMHIs for youth, less is known about how adolescents who engage in self-injury understand their experiences and use digital technologies, including emerging tools such as artificial intelligence (AI), to support their mental health. This study explored adolescents’ lived experiences of self-injury, help-seeking behaviors, and technology use for coping and support. Methods We conducted semi-structured interviews between May 2024 and April 2025 with 21 adolescents (14–18 years old) with lived experience of self-injury. Recruitment occurred through a mental health screener hosted on a large national mental health nonprofit's website. Interviews explored adolescent experiences with self-injury, barriers to seeking help, and the role of digital tools in their self-injury self-management. Interviews were audio-recorded, transcribed, and analyzed via thematic analysis. Results Adolescents described self-injury as a coping strategy embedded within broader emotional and social stressors. While they were aware of the harms, they commonly expressed ambivalence about stopping the behavior. Stigma and concerns about disclosure often limited help-seeking and contributed to their use of digital technologies to access information and support. Participants reported using a range of tools, including music streaming platforms, journaling and mood-tracking apps, online communities, and AI systems such as ChatGPT to regulate emotions, reflect on their experiences, seek advice, and discuss sensitive topics. Although these technologies were valued for their accessibility, privacy, and immediacy, participants also highlighted limitations, including inaccurate or generic AI responses, limited moderation in online communities, and the complex emotional impacts of music. Conclusion Our findings underscore the complex and evolving role digital technologies, including AI, play in adolescents’ experiences of self-injury, coping, and help-seeking. These insights have important implications for the development of future interventions and for clinicians, caregivers, and other health professionals supporting adolescents’ mental health.